PROFITABILITAS, LEVERAGE DAN PERTUMBUHAN PERUSAHAAN DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Leni Herlina; Ardi Hidayat (Universitas Bina Bangsa, 2021)
The company has a goal to prosper the shareholders through increasing the value of the company which can describe the state of the company. The purpose of this study is to determine whether the level of profitability, leverage and company growth an effect on the value of the company in service companies the construction and building sub sector listed on the Stock Exchange Indonesia for the period of 2014-2020. The research method used is quantitative. The population used is the construction and building sub sector companies on the Indonesia Stock Exchange totaling 20 companies with a total of 6 samples and 42 data obtained (6 companies x 7 years of observation), while the buckling of the sample using the purposive sampling method. The result of the partial hypothesis test research that profitability and company growth have an effect on company value, and leverage has no effect on company value. While simultaneously it isconcluded that profitability, leverage and company growth effect company value